Implementing Jigsaw Model with Learning Cards to Improve Fifth Graders’ Natural Resources Learning Outcomes in Surabaya - Resdiana; Jane Koswojo (SEJ (Science Education Journal), 2026)
This action research aims to improve student learning outcomes in the subject of Natural Resources (SDA) in Indonesia by applying the jigsaw learning model combined with learning cards. This combination is rarely used in the context of action research in natural and social science learning in elementary schools. The study was conducted using the Kemmis and McTaggart spiral model in two cycles, covering the stages of planning, action implementation, observation, and reflection. The research subjects were 34 students in class VA of Santa Maria Elementary School in Surabaya. Data were collected through learning outcome tests, observations of student and teacher activities, and field notes. The results showed a significant increase in academic achievement, with the average score increasing from 66.61 in the first cycle to 93.32 in the second cycle, and learning completeness rising from 38.2% to 97.1%. Student activities during learning also showed improvement, especially in cooperation, individual responsibility, and the ability to explain the material. The application of Jigsaw, supported by learning cards, aligns with constructivism, cognitivism, and meaningful learning theories that emphasise the process of knowledge construction through interaction and elaboration. By combining cooperative techniques and simple visual media, this study makes a new contribution: a practical, structured, and easily replicable action model to improve science and social studies learning in elementary schools.